2023
DOI: 10.1038/s41467-023-37042-6
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of transmembrane and cytoplasmic juxtamembrane regions of Toll-like receptors

Abstract: Toll-like receptors (TLRs) are the important participants of the innate immune response. Their spatial organization is well studied for the ligand-binding domains, while a lot of questions remain unanswered for the membrane and cytoplasmic regions of the proteins. Here we use solution NMR spectroscopy and computer simulations to investigate the spatial structures of transmembrane and cytoplasmic juxtamembrane regions of TLR2, TLR3, TLR5, and TLR9. According to our data, all the proteins reveal the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Among the PRR family, Toll-like receptors have received more attention and investigation because of their significant function in host defense and involvement in a number of pathological processes, such as acute lung injury (ALI), and sepsis ( Lafferty et al., 2010 ; Vijay, 2018 ). TLRs are type I transmembrane proteins composed of three domains including I) an extracellular leucine-rich repeat (LRR) domain that mediates recognition of PAMPs, II) a trans-membrane domain, and III) a cytoplasmic Toll-interleukin 1 receptor (TIR) domain which triggers downstream signaling ( Figure 2 ) ( El-Zayat et al., 2019 ; Kornilov et al., 2023 ).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Among the PRR family, Toll-like receptors have received more attention and investigation because of their significant function in host defense and involvement in a number of pathological processes, such as acute lung injury (ALI), and sepsis ( Lafferty et al., 2010 ; Vijay, 2018 ). TLRs are type I transmembrane proteins composed of three domains including I) an extracellular leucine-rich repeat (LRR) domain that mediates recognition of PAMPs, II) a trans-membrane domain, and III) a cytoplasmic Toll-interleukin 1 receptor (TIR) domain which triggers downstream signaling ( Figure 2 ) ( El-Zayat et al., 2019 ; Kornilov et al., 2023 ).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…TLRs are essential for activating the innate immune response and initiating adaptive immunity ( Fitzgerald and Kagan, 2020 ; Duan et al., 2022 ). TLRs are characterized by sharing an extracellular leucine-rich repeat (LRR) region and an intracellular TIR structural domain ( Kawasaki and Kawai, 2014 ; Kornilov et al., 2023 ). The LRR structural domain is responsible for binding to PAMP, and the TIR structural domain is responsible for binding to TIR structural domains containing adapter molecules, including MyD88, TIR domain-containing adapter (TIRAP), TRIF, TRIF-related adapter molecule (TRAM), and sterile alpha and HEAT-Armadillo motifs (SARM), to initiate signaling ( Brikos and O'Neill, 2008 ; Cui et al., 2014 ).…”
Section: Role Of Tlrs In Brucella Infectionmentioning
confidence: 99%
“…With the use of the NMR experiment, the authors confirmed that the computationally obtained two modes correspond to distinct conformations of the BB-loop and that Zn binding may affect the dynamics and conformational landscape of the BB-loop in the TIR domain. Another example of the use of solution NMR combined with computational simulations has been recently published . Kornilov et al contributed to resolving one of the major “blank spots” in the structure of TLRs, which was the conformation of their transmembrane domains and cytoplasmic juxtamembrane (JM) regions.…”
Section: Available Structures Of Tlrsmentioning
confidence: 99%